Minimizing the Psychological Impact of the Covid-19 Pandemic on Vulnerable Groups: Elderly and Mental Disorders Through Family Psychoeducation - Daulay, Wardiyah; Nasution, Mahnum Lailan; Sri Eka Wahyuni (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The increase in the number of COVID-19 cases has had a negative impact on everyone's mental health, including vulnerable groups of the elderly and people with mental disorders. This is because the elderly and people with mental disorders have difficulty adjusting and are unfamiliar with their social environment. The purpose of this service is to provide support through family psychoeducation to minimize the psychological impact on vulnerable groups. Lecture and discussion methods are used to increase family knowledge in caring for the elderly and mental disorders. To measure the psychological condition of the vulnerable group, the SRQ-20 questionnaire was used and analyzed statistically (dependent t-test). Role play and simulation methods are used to improve family skills in caring for, managing burdens and utilizing health services. The results showed that there was an influence of psychoeducation on the psychological condition of the elderly with p-value <Î± (0.04<0.05), and for the mental disorder group it also showed that the treatment given in the form of family psychoeducation therapy gave benefits to psychological conditions with p-value <Î± (0.00). <0.05). This therapy is proven to be effective because it can provide information on the ability of families experiencing distress, provide education to them to improve their ability to understand and have strong coping so that problems do not occur in family relationships.